A-Z, how to deal with a COVID-19 pandemic and emergency according to the Quran and sunnah? - Wahid, Suhail (Usuli Faqih Research Centre PLT, 2024)
This research addressed preparing Islamic guidance based on the Quran and sunnah in preventing and controlling a pandemic and managing emergencies, employing inductive and analytical research approaches. This research will adopt COVID-19 as the main focal point to prepare guidance due to its severity compared to other pandemics throughout world history. The lack of proper guidance based on the Quran and sunnah during COVID-19 outbreaks and emergencies has led to serious catastrophic cases such as the Tablighi cluster, late intervention from the government in containing the pandemic, and disobedience towards authorities’ orders during the COVID-19 outbreak. This research employs a qualitative method in which the results of the research are obtained through a literature review to acquire the Quran and sunnah approach in dealing with the pandemic and emergency. The results of the analysis indicated that good preventive measures such as obeying authorities, seeking medical treatment, and self-cleanliness could be adapted to prevent the pandemic from worsening. Furthermore, efficient leadership, management, and strategies will help control the worst scenario during an emergency. All parties from the higher and lower hierarchy must be held responsible if the same event occurs in the future.